Stakeholder Value: A Convenient Excuse for Underperforming Managers? - Flugum, Ryan; Souther, Matthew E. (Journal of Financial and Quantitative Analysis, 2025)
Abstract Firms falling short of earnings expectations are more likely to cite stakeholder-focused objectives in their public communications following earnings announcements. This behavior is consistent with managers preferring to be evaluated by subjective stakeholder-based performance criteria when falling short on objective shareholder-based measures. This increased use of stakeholder language is most evident among firms narrowly missing earnings estimates and appears unrelated to a firm’s actual environmental, social, and governance (ESG)-related activity. Stakeholder language appears to influence the evaluation of CEOs; turnover–performance sensitivity is lower for managers citing stakeholder value. Collectively, our findings are consistent with concerns that stakeholder objectives reduce managerial accountability for poor performance.